GAMBARAN STATUS GIZI ANAK DENGAN PENYAKIT JANTUNG BAWAAN - Rahmi Maulia; Riri Novayelinda; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Congenital Heart Disease (PJB) is one of congenital abnormalities with abnormalities in structures and circulatoryfunctions that have been present since birth. Children with congenital heart disease are often disrupted by their dietaryintake and have an impact on their growth. Anthropometry is a way to determine the nutritional status of one of them byusing the parameters of age, weight, and height. Anthropometric measurements can use Weight per Age (BB / U), BodyHeight per Age (TB / U), Weight Loss per Body Height (BM) and Body Mass Index (BMI / U). The purpose of this studyis to see the picture of nutritional status in children with congenital heart disease (CHD) in one private hospital inPekanbaru. The type of this research is descriptive research with total sampling method. The result of this researchwere taken using by observation sheet and medical record data of patients with congenital heart disease. The results ofthis study obtained 55 samples with total sample. The measuring instruments used are weighing scales and body lengthmeasuring instruments. The analysis to know the frequency distribution. The results showed that 47 respondents whostudied non-cyanotic congenital heart disease category had the most normal nutritional status of 33 respondents(70.2%) and 1 obese nutritional status (2,1%), so it can be concluded that the majority of status of nutritional childrenwith non-cyanotic congenital heart disease is normal status. Researchers recommend to their parents to maintain abalance of nutritional intake and monitor the growth of children with congenital heart disease.Keywords : Child, Congenital heart disease, Nutritional status.